"Forest Ag": encouraging forest productivity - Colorado State Forest Service, author (Colorado State University. Libraries, 2007)
In 1990, the Colorado legislature enacted House Bill 1229, now recorded in Title 39 of the Colorado Revised Statutes. This statute allows certain forest lands similar tax valuation as that of traditional agricultural lands. Qualified landowners with 40 or more forested areas and who are interested in harvesting wood products from their lands may participate in this program.
Forest Ag: encouraging forest productivity
CSFS #150-599.
Keywords: forested land; annual work plan; forest management plan; forest trees; tangible wood products; Colorado